The Relationship between Blood Glucose Levels and Sleep Quality in Patients with Diabetes Mellitus - Friska Friska; Eri Fazriani (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabetes mellitus is a public health problem with high morbidity and mortality rates worldwide. DM is predicted to increase in 2030 by 643 million people and in 2045 by 783 million people. Diabetes is characterized by an increase in blood glucose levels, with frequent micturition and excessive thirst at night which makes diabetics experience sleep disturbances and has an impact on the quality of sleep of diabetics. Objectives: to determine the relationship of blood glucose levels to the quality of sleep of patients with diabetes mellitus. Methods: Quantitative research using a correlational design with a cross sectional approach. The number of samples in this study was 64 people. The research instrument used a questionnaire and a blood sugar level checker as a screening of current blood sugar levels in patients with diabetes mellitus. Data analysis using the spearman rank test. Results: The majority of respondents were female with an age range of 51-60 years and had high blood glucose levels >200mg/dL by 89.1%, and poor sleep quality by 67.2%. In this study there was a significant relationship between blood glucose levels and sleep quality with a value of ρ value = 0.0001 (<0.05). Conclusion: Symptoms of diabetes mellitus due to increased blood glucose levels can worsen the quality of sleep of people with diabetes mellitus.